The dynamic evolution of synergies between BIM and sustainability: A text mining and network theory approach. (May 2021) - Al Hattab, Malak
Abstract: The increasing demand for a sustainable Architecture, Engineering and Construction (AEC) industry has driven research domains integrating Building Information Modeling (BIM) with sustainability to gain momentum over the past years. While some studies have reviewed the development in these two domains separately, they did not address the important associations between them, nor did they analyze their joint advancement over time. Therefore, this study aims to understand and quantitatively analyze the dynamic evolution of relationships between BIM and sustainability critical towards developing BIM's functionalities to satisfy the industry's growing sustainability needs. First, 523 relevant journal articles published over the last 15 years were collected. Rule-based content analysis is then conducted on these articles using text mining to retrieve and structure relevant textual data pertaining to the six defined dimensions: BIM functionalities, software, sustainability aspects, green certification systems, project phases, and stakeholders. Social network theory is then applied to map and measure the associations between the dimensions' components for analyzing the dynamic changes in their synergies over three spans. Results reveal a significant transformation in the diversity, magnitude, and expansion of associations between BIM and sustainability domains across the supply chain. Findings also highlight less explored areas that require further research and industrial attention towards achieving full use of BIM and sustainability's integrated power. This work's novelty lies in comprehensively and quantitatively analyzing these often-dismissed synergies to reveal through knowledge-based findings how BIM has progressed to address the industry's changing sustainability requirements and recommend future directions for advancing sustainable BIM practices. Highlights: Changes in synergies between BIM and sustainability in AEC research are analyzed. Text mining and network theory are utilized to map synergies between 2005 and 2020. Results show the most and least prominent research areas across multiple dimensions. Findings are discussed and future research and industry directions are recommended.